Behavior - Landscape Interactions May Create Super-Spreader Environments: Vigilance-Olfactory Interactions Across Land Type and Disease Transmission Potential in the Banded Mongoose - Alexander, Kathleen Anne; Nichols, Carol Anne (Frontiers in Ecology and Evolution, 2020)
A complex suite of drivers can influence infectious disease transmission with behavior and landscape spatial dynamics contributing importantly to epidemic patterns across host-pathogen-environmental systems. However, our understanding of the interaction between landscape and host behavior and its influence on spatial variability in pathogen transmission is limited. In the banded mongoose (Mungos mungo), a novel tuberculosis pathogen, Mycobacterium mungi, has emerged in Northern Botswana, which is transmitted through olfactory communication behaviors. We evaluated how associations between landscape type and mongoose behaviors affect the frequency of olfactory communication behaviors and pathogen transmission potential. We used remote sensing camera traps at den sites to eliminate observer influence across human-modified and natural landscapes (n=18 troops, 18,229 detections of banded mongooses from 7,497 photographs). Using generalized linear mixed models, we identified a significant effect of vigilance and the interactions between vigilance and landscape and vigilance and troop count on the frequency of olfactory behaviors. Interactions between troop count-vigilance interactions had a negative influence on olfactory communication. Vigilance, however, appeared to have a bidirectional association with olfactory communication depending on land type. In lodge areas, vigilance was associated with increased olfactory behaviors, but in landscapes with expected increases in predation risk (i.e., national park and urban land-use areas), vigilance had a negative association with olfactory behaviors. The interaction between behavior and landscape type may have the potential to create “super-spreading” environments, or transmission hotspots, where behavior-landscape interactions increase pathogen shedding and transmission potential.